ByzRev 06.2024.072: Kaya Şahin, Peerless among princes: the life and times of Sultan Süleyman.: Oxford: Oxford University Press, 2023. - Kraft, András (The Byzantine Review, 2024)
Kaya Şahin, Peerless among princes: the life and times of Sultan Süleyman. Oxford: Oxford University Press 2023. XIV + 384 pp. – ISBN 978-0-19-753163-1